Cultural Reform Through Community Policing: Building Police and Community Partnership Based on Social Capital - Girindra, Putu; Arsa, Dimas (Indonesian National Police Academy, 2025)
This study examines the implementation of the community policing approach or Community Police (Polmas) in order to build a partnership between the POLRI institution and the community in maintaining public trust. Normatively, this approach is indeed firm and optimal, but culturally as proposed by Pierre Bourdieu in the theory of social capital, in terms of habitus , Indonesian society has not been able to apply the community policing approach optimally due to the weak social strength of the community. The results of the analysis illustrate that the challenge of implementing this community policing approach is the remnants of the paramilitary policing paradigm or military-style arrangements that are still inherent in society in general. Therefore, the transformation of the implementation of the community policing approach will not have a significant impact if it is only implemented at the surface level or normatively, but must be able to touch the deepest layer, namely cultural transformation.